Hydrogen economy as a strategic priority for Ukraine's recovery - Dmitriieva , Oksana; Dmitriieva, Diana (Global Prosperity, 2023)
This article provides an overview of the state of the hydrogen economy in Ukraine, including the country's resources for hydrogen production, the current state of hydrogen projects, funding sources for the development of the hydrogen economy, and proposals for the future development of the hydrogen industry in Ukraine. Ukraine has significant potential for the development of a hydrogen economy, with abundant resources for the production of hydrogen. However, the development of the hydrogen economy in Ukraine faces several challenges, including the need for investment in research and development, infrastructure development, and technology deployment. To support the development of the hydrogen economy in Ukraine, the government needs to establish a comprehensive plan for the development of a hydrogen infrastructure, increase incentives for the adoption of hydrogen technologies, and foster international partnerships. Overall, the successful development of the hydrogen economy in Ukraine will require a coordinated effort between government, industry, and academia to advance the state of hydrogen technologies and infrastructure, build a skilled workforce, and create incentives for the adoption of hydrogen technologies. The purpose of the article is to identify the status and prospects of the development of the hydrogen economy as a strategic priority for Ukraine's recovery. Achieving this goal involves solving such tasks as analyzing the state of development and scientific substantiation of strategic directions for further prospects for the formation of the hydrogen economy in Ukraine. The hydrogen economy has become an increasingly important topic in recent years as countries around the world seek to transition to a more sustainable energy system. Ukraine, like many other countries, has recognized the potential of hydrogen as a clean and renewable energy source and made it a strategic priority for its economic recovery. The global hydrogen economy envisions a significant transformation of the current energy system with a focus on sustainability, efficiency, and cooperation to meet the energy needs of the world's population while reducing greenhouse gas emissions and contributing to a more sustainable future. The hydrogen economy in Ukraine is still in the early stages of development, but some efforts have been made recently to promote its growth.